Research on tribological characteristics of bevel gear after shot blasting based on 85-pellets model. (July 2019) - Mo, Shuai; Feng, Zhanyong; Jin, Guoguang; Zhang, Ting; Ma, Shuai; Shang, Xinyu; Houjoh, Haruo
High-speed overloading puts forward very strict requirements on the bending strength of spiral bevel gears, and shot blasting is a technological process method to increase gear bending fatigue strength significantly. During the process of shot blasting, a large number of tiny pellets bombard metal target material surface at very high speed in order to let the target material form plastic deformation and form strengthened layer at the same time. As the bombarded target, the microstructure of gear surface spiral bevel gear is inevitably changed. This paper aims at revealing how the shot peened surface microstructure of the spiral bevel gear affects lubrication of gear and establishes a reasonable microstructure description model of the shot blasting surface of the spiral bevel gear, revealing the tribological characteristics of spiral bevel gears after shot blasting treatment based on the elastohydrodynamic lubrication theory. Also, comparative research is carried out on a variety of lubrication characteristics of the microstructure surface.